The Impact of Customer Experience and Security on Customer Satisfaction in Shopee Mobile E-Commerce in Surabaya - Hirzy Attirafi; Zawawi Zawawi (Majapahit Journal of Islamic Finance and Management, 2025)
Along with the rise in mobile device usage, mobile applications have become crucial in enhancing the e-commerce ecosystem. Shopee is one of the most popular e-commerce platforms among Indonesian users. This study seeks to explore how the quality of customer experience and security affects customer satisfaction. Employing a quantitative survey approach, data were gathered from 88 respondents chosen through purposive sampling. Partial Least Square (PLS) analysis was applied to assess validity, reliability, and test the hypotheses. Findings reveal that both user experience and security significantly and positively impact customer satisfaction. A better user experience typically leads to greater satisfaction, and higher perceived security likewise elevates customer satisfaction when shopping on Shopee.